2022
DOI: 10.1111/bju.15885
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial of intravesical electrical stimulation for underactive bladder

Abstract: To evaluate the efficacy and safety of intravesical electrical stimulation (IVES) performed with a novel device in patients with underactive bladder (UAB). Patients and MethodsThis was a multicentre, prospective, single-blind, randomized controlled clinical trial of patients with UAB in China. Eligible patients were randomly assigned in a 1:1 ratio to receive conventional IVES (n = 38) or IVES with an open circuit (n = 38). The primary efficacy measure was change from baseline in post-void residual urine volum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
0
3
1
3
Order By: Relevance
“…Compared to the findings of this study, which demonstrated no statistically significant changes in the ND group, previous studies conducted by Liao et al 10 and Deng et al 11 showed positive effects in patients who might have problems in impulse transmission that involve the micturition reflex pathway, such as those with spinal cord injury, spinal canal stenosis, and postoperative lumbar disc herniation.…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…Compared to the findings of this study, which demonstrated no statistically significant changes in the ND group, previous studies conducted by Liao et al 10 and Deng et al 11 showed positive effects in patients who might have problems in impulse transmission that involve the micturition reflex pathway, such as those with spinal cord injury, spinal canal stenosis, and postoperative lumbar disc herniation.…”
Section: Discussioncontrasting
confidence: 98%
“…Improvements in urinary flow, post-voiding residual, voiding efficiency, and first sensation volume during the bladder filling phase were observed in the evaluation of urodynamic parameters following the IVES procedure. 10 , 11 In this study, we evaluate the efficacy of IVES by comparing urodynamic parameters before and after the IVES procedure. In previous studies, efficacy assessment was done by observing clinical changes in clean intermittent catheterization (CIC) status and subjective assessments of quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, patients with UAB received IVES treatments using an FES-D1 stimulator and a DJ-A01 stimulating electrode (General Stim, Inc., Hangzhou, Zhejiang, China) ( Fig. 1 ) [ 19 ]. For the IVES procedure, a sterile, disposable 12F transurethral catheter with a DJ-A01 stimulating electrode was inserted into the bladder, which was then filled with 150 mL of body-temperature (37°C) sterile saline.…”
Section: Methodsmentioning
confidence: 99%
“…Die IVES wird zumeist in Therapiezyklen von 5 aufeinanderfolgenden Tagen für 3-4 Wochen angewendet [47]. Die Therapiedauer einer einzelnen Anwendung dauert zumeist 90 Minuten [43], es werden aber auch kürzere Therapiesitzungen durchgeführt [47].…”
Section: Intravesikale Elektrostimulation (Ives)unclassified